Post-program Monitoring : Proposed Decision on Countries. (Policy Papers; Policy Paper ;, 2016)
On July 1, 2016 the Executive Board adopted a decision to move to a more risk-based and focused framework for Post-Program Monitoring (PPM). The revised decision on PPM, which comes into effect on September 30, 2016, specifies absolute size and quota-based thresholds for establishing expectations as to when members would engage in PPM. Under the new framework, members would be expected to engage in PPM if their credit outstanding exceeds at least one of the applicable thresholds, unless the Managing Director considers that, in her view, the member's circumstances are such that the process is unwarranted. Against that backdrop, this paper contains proposals to operationalize the new PPM decision.